Comunidade bacteriana em viveiros de aquicultura - Silva, Daniele Belarmino da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this study was identify the bacterial communities in dynamic of the sediment. In this study, we compared the bacterial communities present in sediment of two fish farm pond a used as water reservoir (V1) and the other with conditions of high nutrient load (V4), which are inserted in a sequential system with continous water flow (six ponds). The sediment sampling were conducted in two distinct periods one in dry season (July and August/2012) and another in the rain (January and February/2012). The bacterial community was assessed by sequencing the 16S rRNA. Through this data we observed in V1 regardless of time of year the bacterials phyla remained virtually unchanged.In V4 samples, was observed a variation in the frequency of organisms found in relation to different collections. In V1 was the predominance of the Phylum Firmicutes followed Proteobacteria, Acidobacteria and Actinobacteria. The largest number of sequences found at V4 belonged to the Proteobacteria phylum followed Acidobacteria, Firmicutes, Actinobacteria, Chloroflexi, Nitrospira, Gemmatimonadetes and TM7. A comparison of the bacterial population of the two ponds studied at different times showed that the bacteria at these sites varies according to the climatic conditions and are closely linked with nutrient concentration local. These differences are important in elucidating the role played by prokaryotes in the sediment dynamics

O trabalho objetiva avaliar o papel da comunidade bacteriana na dinâmica dos sedimentos. No presente trabalho, compararam-se as comunidades bacterianas presentes em sedimentos de dois viveiros de piscicultura, um reservatório de água (V1) e o outro com condições de elevada carga orgânica (V4), os quais estão inseridos em um sistema sequencial com fluxo contínuo de água. As coletas de sedimentos foram realizadas em dois períodos distintos, um sendo na seca (Julho e Agosto/2012) e outro na chuva (Janeiro e Fevereiro/2012). A comunidade bacteriana foi avaliada através do sequenciamento do gene 16S rRNA. Os filos bacterianos permaneceram praticamente inalterados nas amostras V1 comparadas nas duas épocas estudadas. Nas amostras do V4 observou-se variação na frequência dos organismos encontrados em relação às diferentes coletas. A predominância em V1 foi dos filos Firmicutes seguido do Proteobacteria, Acidobacteria e Actinobacteria. No V4, o maior número de sequências encontradas pertencia ao filo Proteobacteria, seguido de Acidobacteria, Firmicutes, Actinobacteria, Chloroflexi, Nitrospira, Gemmatimonadetes e TM7. A comparação da população bacteriana dos dois viveiros estudados em diferentes épocas mostrou que as bactérias variam de acordo com as condições climáticas e estão intimamente interligadas com a concentração de nutrientes do local. Estas diferenças são importantes na elucidação do papel desenvolvido pelos procariotos na dinâmica dos sedimentos
Keywords: Aquicultura; Peixe - Criação; Viveiros; Genes; Bactérias; Microbiota; Genomas; Genomes